2020
DOI: 10.1038/s41588-020-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of cell types underlying brain complex traits yields insights into the etiology of Parkinson’s disease

Abstract: Genetic identification of cell types underlying brain complex traits yields insights into the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
271
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(315 citation statements)
references
References 81 publications
42
271
1
1
Order By: Relevance
“…By integrating genetics and single-cell expression data, we found that PD risk is linked to expression specificity patterns in dopaminergic neurons, serotonergic neurons, and radial glia, suggesting that these cell types disrupt biological networks that impact PD risk. Although our study failed at replicating specific enrichment patterns for oligodendrocytes and microglia as previously reported using other approaches [18], our results are in concordance with previous literature that applies various methodologies to gain similar conclusions [5].…”
Section: Discussionsupporting
confidence: 93%
“…By integrating genetics and single-cell expression data, we found that PD risk is linked to expression specificity patterns in dopaminergic neurons, serotonergic neurons, and radial glia, suggesting that these cell types disrupt biological networks that impact PD risk. Although our study failed at replicating specific enrichment patterns for oligodendrocytes and microglia as previously reported using other approaches [18], our results are in concordance with previous literature that applies various methodologies to gain similar conclusions [5].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to human genetics, the canine behavioral GWAS's with and without control for body Our scRNA-seq findings are supported by studies that used human GWA genesets from diverse traits to identify relevant cells in scRNA-seq data 75 . For instance, educational attainment and schizophrenia showed a Spearman rank correlation of cell-type association of 0.94 because both were enriched for telencephalon projecting excitatory neurons out of the 39 cell types queried, and both associations were enriched for neurogenesis and synaptic processes genes.…”
Section: Discussionmentioning
confidence: 71%
“…Recent single-nuclei transcriptomics in the substantia nigra support association of PD with dopaminergic neuron-specific gene expression and, interestingly, implicate oligodendrocyte-specific expression [ 39 ]. Similar single-cell transcriptomics in the mouse nervous system also confirm the association between dopaminergic neurons and PD, and reiterate the novel association with oligodendrocytes [ 40 ]. Additionally, the pathway analysis study mentioned previously integrated single-cell expression data to link PD risk to expression patterns in dopaminergic neurons, serotonergic neurons, hypothalamic GABAergic neurons and neural progenitors [ 38 ].…”
Section: Utilizing Genetic Risk Profiling To Identify Biological Pmentioning
confidence: 69%